Nigerian agricultural research: review and recommendations - Herrmann, Omer Wesley ([East Lansing] Consortium for the Study of Nigerian Rural Development [Michigan State University], 1968)
The research covers the following areas: soil fertility in the tropics; livestock research centre for West Africa; high protein grains and legumes; agricultural economics and rural sociology; and food science research
osc 30/01/2019
Arch
Keywords: Agriculture; Nigeria